Supplementation of Hermetia illucens Larvae in Poultry By-Product Meal-Based Barramundi, Lates calcarifer Diets Improves Adipocyte Cell Size, Skin Barrier Functions, and Immune Responses - Chaklader, Md Reaz; Howieson, Janet; Fotedar, Ravi; Siddik, Muhammad A. B. (Frontiers in Nutrition, 2021)
A 6-week feeding trial was performed to examine the effects of supplementing Hermetia illucens (HI) larvae meal when fishmeal (FM) was replaced with poultry by-product meal (PBM) in juvenile barramundi, Lates calcarifer diet. The effect was evaluated in terms of barramundi growth, filet quality, internal tissue structure, serum biochemistry, skin neutral mucins, immune response, and resistance to Vibrio harveyi. Three isonitrogenous (48% crude protein) and isolipidic (18% crude lipid) diets: an FM-based diet (control) and two diets containing 60 and 75% of PBM supplemented with 10% HI larvae (60PBM + HI and 75PBM + HI) were formulated. A total of 225 barramundi, with an average weight of 15.87 ± 0.14 g, were randomly distributed into nine tanks, each holding 25 fish. There were no significant effects of test diets on growth, but feeding HI-supplemented PBM diets significantly increased the survival rate. A significantly reduced intraperitoneal fat index in HI-supplemented-PBM-fed fish was correlated to a decreased size of peritoneal adipocytes. The observation of no histopathological alteration of the liver in the HI-supplemented-PBM-fed fish was further supported by significant alterations in serum biochemistry, in particular, a decreasing tendency of alanine transaminase, glutamate dehydrogenase, and total bilirubin. A 14-day challenge with V. harveyi indicated that HI-supplemented PBM diets reduced the infection rate in barramundi. After 24 h of infection, increased serum (lysozyme) and skin barrier functions, down-regulation of interleukin-1beta, and upregulation of interleukin-10 were found in HI-supplemented-PBM-fed fish.